(untitled) (Revista de Ensino em Artes, Moda e Design, 2021)
The present study is an aesthetic, sensitive and feminist analysis of the production of clay handicrafts by a master-artisan from the community of Alto do Moura, Caruaru, Pernambuco. The process of analysis and investigation refers to the works of the master artisan Marliete Rodrigues, considering that understanding the aesthetic, sensitive, symbolic and subjective recurrences present in the artistic production of women artisans can evidence the imaginary that is constituted from the daily socio-cultural experiences of women. artists on gender issues. From a given phenomenological dimension, we seek to answer questions such as: What is the centrality of the aesthetic and sensitive elements in the artisan’s works? Which elements of gender and linked to the daily life of the community are materialized through the symbols present in the analyzed works? Is it possible to characterize as a feminist the aesthetic that develops from the imaginary and is expressed in your works? The results obtained show that although, at first glance, the master’s work seems to be inscribed in a kind of compulsory femininity, due to the recurrent use of elements related to flowers, modesty in clothing and the actions of the women portrayed, Marliete’s work is reveals dissent by proposing subtle ruptures in the structures from which the clay art of the Alto do Moura community is constituted.